Fluctuating illuminance pattern of tubular fluorescent daylight in 30-minute versus 8-hour measuring duration - Chen, Ai-Hong; Majid, Amirul Ad-din (Science, Engineering and Health Studies, 2021)
This study aimed to investigate the fluctuating illuminance pattern of tubular fluorescent daylight (CT 6200K). The first investigation focused on the changes within the first 30 minutes in a 1-minute interval while the second investigation examined the changes over 8 hours duration with a 1-hour interval. Luxmeter was used to measure the illumination in pre determined geometrical points in specific room sizes. Illuminance took approximately 5 minutes to reach the peak before it started to deteriorate with time (rs(28) = -0.715, p<0.05). Then, the illuminance seemed to stabilize after the luminaires were turned on for 15 minutes. A similar decreasing pattern was found in the 8-hour duration (r(6) = -0.785, p<0.05) at multiple measurement points (F(1.540, 15.398) = 36.804, p<0.05). The recommendation for lighting experiments involving tubular fluorescent light is to start measurement only after the luminaires were turned on for 15 minutes and could be continuously measured for 4 hours.